Molecular Monitoring in Acute Myeloid Leukemia Patients Undergoing Matched Unrelated Donor - Hematopoietic Stem Cell Transplantation: Single Center Experience - Panovska Stavridis, Irina; Pivkova Veljanovska, Aleksandra; Ridova, Nevenka; Stojanoski, Zlate; CHadievski, Lazar; Trajkova, Sanja; Popova-Labacevska, Marija; Matevska-Geshkovska, Nadica; CHevrevska, Lidija; Georgievski, Borche; Dimovski, Aleksandar (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2020)
Minimal residual disease (MRD) assessment in acute myeloid leukemia (AML) cases is a complex, multi-modality process and, though much of its clinical implications at different points are extensively studied, it remains even now a challenging area. It is a disease the biology of which governs the modality of MRD assessment; in patients harboring specific molecular targets, high sensitivity techniques can be applied. On the other hand, relapse is considered as the leading cause of treatment failure in AML patients undergoing allogeneic hematopoietic stem cell transplantation (alloHSCT).